D6.4 Workplan for transfer of knowledge and experience (update 3) - Antoniou, Theofilos; Krauss, Thomas; Kaskara, Mariza; Buhl, Johanes; Seifert, Patric; Kazadzis, Stelios (My University, 2024)
The deliverable "D6.4 Workplan for Transfer of Knowledge and Experience (update 3)" provides an overview of the capacity building activities implemented under Training Scheme B from June 2023 to October 2024, aimed at enhancing the skills of participants within the ERATOSTHENES Centre of Excellence (ECoE). The report details the diverse training sessions, workshops, and seminars conducted by strategic partners including NOA, DLR, TROPOS, and PMOD/WRC, which focused on thematic areas such as agriculture, disaster risk reduction, atmospheric studies, and remote sensing analysis. Despite challenges such as scheduling and infrastructure limitations, significant progress was made in strengthening institutional expertise through both theoretical and hands-on training, fostering collaborative research efforts, and developing practical skills among participants. The outcomes of these activities are instrumental in advancing ECoE's capacity to conduct high-quality research and contribute effectively to regional environmental management and sustainability. Also, this report outlines the activities planned for the Training Scheme C (November 2024 to June 2026) that will be provided by the advanced partners to ERATOSTHENES research staff.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation